Copper on the Northwest Coast, a biographical approach. (April 2019) - Thompson, L.; Doonan, R.C.P.
Abstract: This paper explores Indigenous use of copper metal to create objects of cultural importance on the Northwest Coast of North America, and the impacts of colonial contact on established cultural practices. Prior to contact (late 17th to early 19th century), native copper and occasional shipwreck drift copper was collected, traded, and used by Indigenous communities to fabricate meaningful objects such as Coppers. Following the introduction of foreign trade materials, copper continued to be used to create culturally significant artefacts but existing frameworks of interaction with the metal shifted to accommodate the new materials and social relations introduced by contact. This investigation highlights the utility of a biographical approach to gain an understanding of Indigenous artefacts and the relationships they engender. Specifically, a close material investigation of a Kwakwaka'wakw Copper fabricated from multiple pieces of metal is conducted. This copper alloy artefact results from a series of material choices, fabrication traditions, and usage that, when considered alongside archaeological and ethnographic data allow us insight in to social, economic, and political changes during the contact period. Highlights: Indigenous copper metal use in the Pacific Northwest through the colonial period Applying an artefact biography framework to the investigation of material culture The use of non-destructive portable X-ray fluorescence in material culture studies